The 3rdWorld Congress on the Integration and Islamicisation of Acquired Human Knowledge - Rahmat, Sarah; Zainuddin, Zarina; Mohammad Aidid, Edre; Hashi, Abdurezak Abdulahi (IIUM Press, 2021)
In June 4th until 6th 2021, IIUM Kuantan has conducted the 3rd World Congress on the Integration and Islamicisation of Acquired Human Knowledge. Unlike the 1st session of the congress which was held in 2013, with the theme of “The Need to Apply the Paradigm of Tawhid as an Alternative to the Secular Paradigm”, and the 2nd session congress that was held in 2016, with the theme “Incorporating Moral Values and Maqasid Al-Shari’ah into Medical and Health Care Practices”, the focus of the 3rd session of WCII 2021 was incorporating ethical values and Maqasid al-Shariah in sustainable healthcare, with the theme “Mental Health and Well-being in the 4th Industrial Revolution”. It served as an academic platform for researchers, scientists and academicians to share their research findings describing traditional and latest applications and practices of medical and health sciences, and the role of moral values and Maqasid al-Shari’ah in harm reduction and sustainable wellbeing in this field.